Riparian Vegetation and Environmental Variables Differ Across Age and Management of Created Wetlands in an Agricultural Landscape - Rose M. Simard; Catherine M. Febria (Environmental Management, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Precision feeding in gestating sows: a retrospective analysis of lysine intake and pregnancy outcomes - P. Langendijk; A.K. Agyekum; F. Simard; M. Richer-Lanciault (Livestock Science, 2025)

The Interactive Role of Climatic Transfer Distance and Overstory Retention on Douglas‐Fir Seedling Survival and Height Growth in Interior British Columbia - Thomson C. Harris; W. Jean Roach; Erin M. Miller; Suzanne W. Simard (Global Change Biology, 2025)
The future climatic niche of interior Douglas‐fir ( Pseudotsuga menziesii var. glauca [Mirb.] Franco) is expected to have little spatial overlap with its current range due to climate change. The resulting misalignment of the climatic niche and species distribution is expected to result in many forests becoming maladapted in their current location, thus increasing vulnerability to disturbance and reducing productivity. This novel study examined the individual and interactive effects of climatic transfer distance and silviculture systems on planted 3‐year‐old Douglas‐fir seedlings across the natural range of interior Douglas‐fir in British Columbia. Several climatic transfer distance variables were considered, and the silviculture systems tested comprised the following gradients of tree retention: 0% retention (clearcut), 10% dispersed retention (seed‐tree), 30% aggregate retention, and 60% aggregate retention with thinning from below. Using linear mixed effect models, we found that survival and height were positively correlated with movements of seedlings to warmer, wetter, and more humid climates. Moisture availability had a stronger influence than temperature, indicating that seedlings transferred to warmer but more arid climates would experience decreased survival and height. Where seedlings were transferred to climates with greater frost frequency or decreased humidity, greater retention of overstory trees improved survival and height. Conversely, movements to more favorable climatic conditions (warmer and wetter) resulted in improved survival and height where overstory retention was low. Our findings suggest that genetic reshuffling of populations through assisted migration could benefit from overstory retention where stressful climatic conditions due to aridity or increased frost frequency occur.

Discharge of ballast residual sediments during de-ballasting procedures: A more realistic estimate of propagule pressure - Nathalie Simard; Andrea M. Weise; André Rochon; Elizabeta Briski; Hugh J. MacIsaac; Christopher W. McKindsey (Marine Pollution Bulletin, 2024)

Human dimensions in shellcraft: tool ownership differentiates taxa utilised and products produced - Thane A. Militz; Nittya S. M. Simard; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2024)
Throughout the Pacific Islands, shellcraft has begun to feature prominently in development intervention which aims to generate positive livelihood outcomes for coastal communities. This activity often involves the post-harvest processing of natural assets, namely shells and skeletal remains of marine taxa, into jewellery by individuals or small-sized enterprises. To foster participation in shellcraft, development intervention commonly involves gifting or subsidising physical assets. Yet knowledge of the natural (i.e., taxa) and physical (i.e., tools) assets required for shellcraft remains scant. An understanding of human dimensions in shellcraft pertaining to patterns in asset use, such as how tool ownership differentiates taxa utilised and products produced, is important for determining if access to a specific tool is necessary, or an encumbrance, for achieving a desired outcome. In this study, we identified tools used and variation in tool ownership among artisans engaged in shellcraft to afford an accurate and realistic understanding of the tools required to participate in this activity. We then evaluate how ownership of a specific tool or type of tool differentiates both taxa utilisation and product production for shellcraft. Results indicate ownership of neither all nor any specific tool was required to participate in shellcraft, with artisans typically owning a unique combination of tools. Furthermore, results identified that some specific tools were critical for affecting the attractiveness of utilising certain taxa or producing certain products. Implications of the significant relationships between specific tools and certain taxa or products are discussed in the context of development intervention and commonly articulated theories of change where shellcraft is linked to subsistence fishing, aquaculture, or tourism.

Regulating cancer risk prediction: legal considerations and stakeholder perspectives on the Canadian context - Palmira Granados Moreno; Terese Knoppers; Ma’n H. Zawati; Michael Lang; Bartha M. Knoppers; Michael Wolfson; Hermann Nabi; Michel Dorval; Jacques Simard; Yann Joly (Human Genetics, 2023)
Risk prediction models hold great promise to reduce the impact of cancer in society through advanced warning of risk and improved preventative modalities. These models are evolving and becoming more complex, increasingly integrating genetic screening data and polygenic risk scores as well as calculating risk for multiple types of a disease. However, unclear regulatory compliance requirements applicable to these models raise significant legal uncertainty and new questions about the regulation of medical devices. This paper aims to address these novel regulatory questions by presenting an initial assessment of the legal status likely applicable to risk prediction models in Canada, using the CanRisk tool for breast and ovarian cancer as an exemplar. Legal analysis is supplemented with qualitative perspectives from expert stakeholders regarding the accessibility and compliance challenges of the Canadian regulatory framework. While the paper focuses on the Canadian context, it also refers to European and U.S. regulations in this domain to contrast them. Legal analysis and stakeholder perspectives highlight the need to clarify and update the Canadian regulatory framework for Software as a Medical Device as it applies to risk prediction models. Findings demonstrate how normative guidance perceived as convoluted, contradictory or overly burdensome can discourage innovation, compliance, and ultimately, implementation. This contribution aims to initiate discussion about a more optimal legal framework for risk prediction models as they continue to evolve and are increasingly integrated into landscape for public health.

Utilization of marine taxa within an artisanal shellcraft sector of the Indo-Pacific region - Nittya S. M. Simard; Thane A. Militz; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2022)
Sustainable utilization of marine taxa is critical for maximizing social and economic goals of livelihood development within the Indo-Pacific. Yet, despite an increasing importance of shellcraft as a livelihood activity within the Indo-Pacific, information on the taxa utilized within shellcraft sectors remains scant. To address this knowledge gap, our study examined diversity, in terms of composition and quantities, of marine taxa utilized by artisan households and, collectively, within an artisanal shellcraft sector of Papua New Guinea. For each taxon, critical source habitats were identified, and the geographic scale of exploitation established. Critically, presented data revealed 73 taxa, representing at least 77 species, were utilized within the studied sector. Many of the taxa utilized had not previously been linked to shellcraft sectors, demonstrating that a broader composition of taxa is utilized than previously acknowledged. In terms of quantity, annual utilization within the sector was close to 500,000 individuals, the majority being mollusks of either class Gastropoda (83.6%), represented by 37 genera, or class Bivalvia (9.6%), represented by four genera. There was a strong bias towards a particular species, Chrysostoma paradoxum (78.5% of all individuals), as indicated by indices for the diversity utilized ( H ′ = 1.23; D = 0.38). However, substantial variation was evident in the diversity of taxa utilized among households ( n = 36) engaged in shellcraft ( H ′ = 1.09 ± 0.71; D = 0.43 ± 0.27), with each household utilizing a unique composition of 19.1 ± 10.6 taxa. Source habitats for taxa ranged from pelagic to benthic intertidal and subtidal substrates, with the geographic scale of exploitation extending to 34 discrete locations up to 417 km away. The array of sector, household, and taxon-specific information presented provides a basis for supporting greater sustainability within shellcraft sectors across the Indo-Pacific, which is discussed within a context of informing community-based resource management, further developing marine aquaculture, and strengthening existing governance.

Experimental Analysis of Survival and Recovery of Ship Fouling Mussels During Transit Between Marine and Freshwaters - Cyrena Riley; David Drolet; Jesica Goldsmit; Jaclyn M. Hill; Kimberly L. Howland; Marie-France Lavoie; Cynthia H. McKenzie; Nathalie Simard; Christopher W. McKindsey (Frontiers in Marine Science, 2022)
Ships and boats may transport whole communities of non-indigenous species (NIS) through hull biofouling, some members of which may become invasive. Several studies have evaluated the diversity of these communities, but very few have analyzed the survival of organisms after their voyages into different and potentially inhospitable conditions. This factor is important to consider because the last port of call approach for risk assessments assumes that if the conditions observed in the last port of call are different from those observed in a receiving port, risks are diminished or null. Using an innovative experimental system, we tested the survival and recovery of the marine blue mussel ( Mytilus edulis ) and the freshwater zebra mussel ( Dreissena polymorpha ) by exposing them to adverse salinity conditions at varying temperatures to simulate ships and boats transiting to ports or marinas with contrasting environmental conditions. Both mussel species, which are well-known for their adaptability to new environments as aquatic NIS, survived better at colder temperatures, with blue mussels surviving up to 14 days in freshwater, and zebra mussels up to 8 days in marine water. This highlights the importance of considering the resistance of fouling organisms to adverse conditions in vector and species risk assessments.

From Past to Present: Construction of a Dataset Documenting Mother-of-Pearl Exports From a Pacific Island Nation, Papua New Guinea - Nittya S. M. Simard; Thane A. Militz; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2021)

Resilience of Rhizopogon-Douglas-fir mycorrhizal networks 25 years after selective logging - Carrie H. Van Dorp; Suzanne W. Simard; Daniel M. Durall (Mycorrhiza, 2020)

Water resource development and sturgeon (Acipenseridae): state of the science and research gaps related to fish passage, entrainment, impingement and behavioural guidance - S. J. Cooke; J. J. Cech; D. M. Glassman; J. Simard; S. Louttit; R. J. Lennox; L. Cruz-Font; C. M. O’Connor (Reviews in Fish Biology and Fisheries, 2020)

Survey of primary care physicians’ views about breast and ovarian cancer screening for true BRCA1/2 non-carriers - S. Pelletier; G. Larouche; J. Chiquette; Z. El Haffaf; W. D. Foulkes; P. Hamet; J. Simard; M. Dorval (Journal of Community Genetics, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Reproductive plasticity of female white-tailed deer at high density and under harsh climatic conditions - Pascale Ayotte; M. Anouk Simard; Steeve D. Côté (Oecologia, 2019)

Seasonal marine mammal occurrence detected from passive acoustic monitoring in Scott Inlet, Nunavut, Canada - Marianne Marcoux; Steven H. Ferguson; Nathalie Roy; Jeannette M. Bedard; Yvan Simard (Polar Biology, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Scaling mangrove aboveground biomass from site‐level to continental‐scale - A. S. Rovai; P. Riul; R. R. Twilley; E. Castañeda‐Moya; V. H. Rivera‐Monroy; A. A. Williams; M. Simard; M. Cifuentes‐Jara; R. R. Lewis; S. Crooks; P. A. Horta; Y. Schaeffer‐Novelli; et al. (Global Ecology and Biogeography, 2016)
Aim We developed a set of statistical models to improve spatial estimates of mangrove aboveground biomass ( AGB ) based on the environmental signature hypothesis ( ESH ). We hypothesized that higher tidal amplitudes, river discharge, temperature, direct rainfall and decreased potential evapotranspiration explain observed high mangrove AGB . Location Neotropics and a small portion of the N earctic region. Methods A universal forest model based on site‐level forest structure statistics was validated to spatially interpolate estimates of mangrove biomass at different locations. Linear models were then used to predict mangrove AGB across the N eotropics. Results The universal forest site‐level model was effective in estimating mangrove AGB using pre‐existing mangrove forest structure inventories to validate the model. We confirmed our hypothesis that at continental scales higher tidal amplitudes contributed to high forest biomass associated with high temperature and rainfall, and low potential evapotranspiration. Our model explained 20% of the spatial variability in mangrove AGB , with values ranging from 16.6 to 627.0 t ha −1 (mean, 88.7 t ha −1 ). Our findings show that mangrove AGB has been overestimated by 25–50% in the N eotropics, underscoring a commensurate bias in current published global estimates using site‐level information. Main conclusions Our analysis show how the ESH significantly explains spatial variability in mangrove AGB at hemispheric scales. This finding is critical to improve and explain site‐level estimates of mangrove AGB that are currently used to determine the relative contribution of mangrove wetlands to global carbon budgets. Due to the lack of a conceptual framework explicitly linking environmental drivers and mangrove AGB values during model validation, previous works have significantly overestimated mangrove AGB; our novel approach improved these assessments. In addition, our framework can potentially be applied to other forest‐dominated ecosystems by allowing the retrieval of extensive databases at local levels to generate more robust statistical predictive models to estimate continental‐scale biomass values.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Temporal and spatial mapping of red grouper Epinephelus morio sound production - C. C. Wall; P. Simard; M. Lindemuth; C. Lembke; D. F. Naar; C. Hu; B. B. Barnes; F. E. Muller‐Karger; D. A. Mann (Journal of Fish Biology, 2014)
The goals of this project were to determine the daily, seasonal and spatial patterns of red grouper Epinephelus morio sound production on the West Florida Shelf ( WFS ) using passive acoustics. An 11 month time series of acoustic data from fixed recorders deployed at a known E. morio aggregation site showed that E. morio produce sounds throughout the day and during all months of the year. Increased calling (number of files containing E. morio sound) was correlated to sunrise and sunset, and peaked in late summer (July and August) and early winter (November and December). Due to the ubiquitous production of sound, large‐scale spatial mapping across the WFS of E. morio sound production was feasible using recordings from shorter duration‐fixed location recorders and autonomous underwater vehicles ( AUVs ). Epinephelus morio were primarily recorded in waters 15–93 m deep, with increased sound production detected in hard bottom areas and within the Steamboat Lumps Marine Protected Area (Steamboat Lumps). AUV tracks through Steamboat Lumps, an offshore marine reserve where E. morio hole excavations have been previously mapped, showed that hydrophone‐integrated AUVs could accurately map the location of soniferous fish over spatial scales of

Multistage gold mineralization at the Lapa mine, Abitibi Subprovince: insights into auriferous hydrothermal and metasomatic processes in the Cadillac–Larder Lake Fault Zone - M. Simard; D. Gaboury; R. Daigneault; P. Mercier-Langevin (Mineralium Deposita, 2013)

Ectomycorrhizal fungal community assembly on regenerating Douglas-fir after wildfire and clearcut harvesting - Jason S. Barker; Suzanne W. Simard; Melanie D. Jones; D. M. Durall (Oecologia, 2013)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

Vertical partitioning between sister species of R hizopogon fungi on mesic and xeric sites in an interior D ouglas‐fir forest - Kevin J. Beiler; Suzanne W. Simard; Valerie LeMay; Daniel M. Durall (Molecular Ecology, 2012)
Understanding ectomycorrhizal fungal ( EMF ) community structure is limited by a lack of taxonomic resolution and autecological information. R hizopogon vesiculosus and R hizopogon vinicolor ( B asidiomycota) are morphologically and genetically related species. They are dominant members of interior D ouglas‐fir ( P seudotsuga menziesii var . glauca ) EMF communities, but mechanisms leading to their coexistence are unknown. We investigated the microsite associations and foraging strategy of individual R . vesiculosus and R . vinicolor genets. Mycelia spatial patterns, pervasiveness and root colonization patterns of fungal genets were compared between R hizopogon species and between xeric and mesic soil moisture regimes. R hizopogon spp. mycelia were systematically excavated from the soil and identified using microsatellite DNA markers. R hizopogon vesiculosus mycelia occurred at greater depth, were more spatially pervasive, and colonized more tree roots than R . vinicolor mycelia. Both species were frequently encountered in organic layers and between the interface of organic and mineral horizons. They were particularly abundant within microsites associated with soil moisture retention. The occurrence of R . vesiculosus shifted in the presence of R . vinicolor towards mineral soil horizons, where R . vinicolor was mostly absent. This suggests that competition and foraging strategy may contribute towards the vertical partitioning observed between these species. R hizopogon vesiculosus and R . vinicolor mycelia systems occurred at greater mean depths and were more pervasive in mesic plots compared with xeric plots. The spatial continuity and number of trees colonized by genets of each species did not significantly differ between soil moisture regimes.

Effects of observed and experimental climate change on terrestrial ecosystems in northern Canada: results from the Canadian IPY program - Gregory H. R. Henry; Karen A. Harper; Wenjun Chen; Julie R. Deslippe; Robert F. Grant; Peter M. Lafleur; Esther Lévesque; Steven D. Siciliano; Suzanne W. Simard (Climatic Change, 2012)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Species patterns in foliar nitrogen concentration, nitrogen content and 13C abundance for understory saplings across light gradients - J. M. Kranabetter; S. W. Simard; R. D. Guy; K. D. Coates (Plant and Soil, 2010)

Effects of growth medium, nutrients, water, and aeration on mycorrhization and biomass allocation of greenhouse-grown interior Douglas-fir seedlings - Olga Kazantseva; Marcus Bingham; Suzanne W. Simard; Shannon M. Berch (Mycorrhiza, 2009)

Access to mycorrhizal networks and roots of trees: importance for seedling survival and resource transfer - François P. Teste; Suzanne W. Simard; Daniel M. Durall; Robert D. Guy; Melanie D. Jones; Amanda L. Schoonmaker (Ecology, 2009)
Mycorrhizal networks (MNs) are fungal hyphae that connect roots of at least two plants. It has been suggested that these networks are ecologically relevant because they may facilitate interplant resource transfer and improve regeneration dynamics. This study investigated the effects of MNs on seedling survival, growth and physiological responses, interplant resource (carbon and nitrogen) transfer, and ectomycorrhizal (EM) fungal colonization of seedlings by trees in dry interior Douglas‐fir ( Pseudotsuga menziesii var. glauca ) forests. On a large, recently harvested site that retained some older trees, we established 160 isolated plots containing pairs of older Douglas‐fir “donor” trees and either manually sown seed or planted Douglas‐fir “receiver” seedlings. Seed‐ and greenhouse‐grown seedlings were sown and planted into four mesh treatments that served to restrict MN access (i.e., planted into mesh bags with 0.5‐, 35‐, 250‐μm pores, or without mesh). Older trees were pulse labeled with carbon ( 13 CO 2 ) and nitrogen ( 15 NH 4 15 NO 3 ) to quantify resource transfer. After two years, seedlings grown from seed in the field had the greatest survival and received the greatest amounts of transferred carbon (0.0063% of donor photo‐assimilates) and nitrogen (0.0018%) where they were grown without mesh; however, planted seedlings were not affected by access to tree roots and hyphae. Size of “donor” trees was inversely related to the amount of carbon transferred to seedlings. The potential for MNs to form was high (based on high similarity of EM communities between hosts), and MN‐mediated colonization appeared only to be important for seedlings grown from seed in the field. These results demonstrate that MNs and mycorrhizal roots of trees may be ecologically important for natural regeneration in dry forests, but it is still uncertain whether resource transfer is an important mechanism underlying seedling establishment.

Influence of soil nutrients on ectomycorrhizal communities in a chronosequence of mixed temperate forests - Brendan D. Twieg; Daniel M. Durall; Suzanne W. Simard; Melanie D. Jones (Mycorrhiza, 2009)

Do escaped transgenes persist in nature? The case of an herbicide resistance transgene in a weedy Brassica rapa population - S. I. WARWICK; A. LÉGÈRE; M.‐J. SIMARD; T. JAMES (Molecular Ecology, 2008)
The existence of transgenic hybrids resulting from transgene escape from genetically modified (GM) crops to wild or weedy relatives is well documented but the fate of the transgene over time in recipient wild species populations is still relatively unknown. This is the first report of the persistence and apparent introgression, i.e. stable incorporation of genes from one differentiated gene pool into another, of an herbicide resistance transgene from Brassica napus into the gene pool of its weedy relative, Brassica rapa , monitored under natural commercial field conditions. Hybridization between glyphosate‐resistant [herbicide resistance (HR)] B. napus and B. rapa was first observed at two Québec sites, Ste Agathe and St Henri, in 2001. B. rapa populations at these two locations were monitored in 2002, 2003 and 2005 for the presence of hybrids and transgene persistence. Hybrid numbers decreased over the 3‐year period, from 85 out of ~200 plants surveyed in 2002 to only five out of 200 plants in 2005 (St Henri site). Most hybrids had the HR trait, reduced male fertility, intermediate genome structure, and presence of both species‐specific amplified fragment length polymorphism markers. Both F 1 and backcross hybrid generations were detected. One introgressed individual, i.e. with the HR trait and diploid ploidy level of B. rapa, was observed in 2005. The latter had reduced pollen viability but produced ~480 seeds. Forty‐eight of the 50 progeny grown from this plant were diploid with high pollen viability and 22 had the transgene (1:1 segregation). These observations confirm the persistence of the HR trait over time. Persistence occurred over a 6‐year period, in the absence of herbicide selection pressure (with the exception of possible exposure to glyphosate in 2002), and in spite of the fitness cost associated with hybridization.

Insertion polymorphism of transposable elements and population structure of Anopheles gambiae M and S molecular forms in Cameroon - M. BOULESTEIX; F. SIMARD; C. ANTONIO‐NKONDJIO; H. P. AWONO‐AMBENE; D. FONTENILLE; C. BIÉMONT (Molecular Ecology, 2007)
The insertion polymorphism of five transposable element (TE) families was studied by Southern blots in several populations of the M and S molecular forms of the mosquito Anopheles gambiae sensu stricto from southern Cameroon. We showed that the mean TE insertion site number and the within‐population insertion site polymorphism globally differed between the M and S molecular forms. The comparison of the TE insertion profiles of the populations revealed a significant differentiation between these two molecular forms (0.163 ST

Methods to control ectomycorrhizal colonization: effectiveness of chemical and physical barriers - François P. Teste; Justine Karst; Melanie D. Jones; Suzanne W. Simard; Daniel M. Durall (Mycorrhiza, 2006)

Metallogeny of the Mont-de-l’Aigle IOCG deposit, Gaspé Peninsula, Québec, Canada - M. Simard; G. Beaudoin; J. Bernard; A. Hupé (Mineralium Deposita, 2006)

Partnering in Oncogenetic Research – The INHERIT BRCAs Experience: Opportunities and Challenges - Denise Avard; Peter Bridge; Lucie M. Bucci; Jocelyne Chiquette; Michel Dorval; Francine Durocher; Doug Easton; Béatrice Godard; David Goldgar; Bartha Maria Knoppers; Rachel Laframboise; Bernard Lespérance; et al. (Familial Cancer, 2006)

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

PCNA Up-Regulation in Cerebral Vessels with Angiotensin II-Hypertension: Abnormal Regulation of Ca2+ Channel and Nitrate Tolerance Associated with Alternative Splicing of cGKI - A. Ivanov; S. Ivanova; L. V. Melnitchenko; V. Gerzanich; M. F. Shuba; J. M. Simard (Neurophysiology, 2003)

Genetic Determinants of Pseudomonas aeruginosa Colonization in Cystic Fibrosis Patients in Canada - M. De Braekeleer; C. Allard; J.-P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genetic determinants ofPseudomonas aeruginosa colonization in cystic fibrosis patients in Canada - M. Braekeleer; C. Allard; J. -P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genotype-phenotype correlation in cystic fibrosis patients compound heterozygous for the A455E mutation - M. De Braekeleer; Christian Allard; Jean-Pierre Leblanc; Fernand Simard; Gervais Aubin (Human Genetics, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Carbon allocation and carbon transfer between t Betula papyrifera and t Pseudotsuga menziesii seedlings using a 13C pulse-labeling method - Suzanne W. Simard; Daniel M. Durall; Melanie D. Jones (Plant and Soil, 1997)

Synthetic peptides corresponding to the F protein of RSV stimulate murine B and T cells but fail to confer protection - M. Trudel; E. J. Stott; G. Taylor; D. Oth; G. Mercier; F. Nadon; C. Séguin; C. Simard; M. Lacroix (Archives of Virology, 1991)

Gene mapping of infectious bovine rhinotracheitis viral DNA genome - Claire Simard; Francine Nadon; Ccile Sguin; Sylvie LaBoissire; M. Trudel (Archives of Virology, 1990)

Comparison of caprine, human and bovine strains of respiratory syncytial virus - M. Trudel; F. Nadon; C. Simard; F. Bélanger; R. Alain; C. Séguin; G. Lussier (Archives of Virology, 1989)